Salmonella contamination risk points in broiler carcasses during slaughter line processing - Rivera-Pérez, Walter (2014)
Salmonella is one of the foodborne pathogens most commonly associated with poultry products. The aim of this work was to identify and analyze key sampling points creating risk of Salmonella contamination in a chicken processing plant in Costa Rica and perform a salmonellosis risk analysis. Accordingly, the following examinations were performed: (i) qualitative testing (presence or absence of Salmonella), (ii) quantitative testing (Salmonella CFU counts), and (iii) salmonellosis risk analysis, assuming consumption of contaminated meat from the processing plant selected. Salmonella was isolated in 26% of the carcasses selected, indicating 60% positive in the flocks sampled. The highest Salmonella counts were observed after bleeding (6.1 log CFU per carcass), followed by a gradual decrease during the subsequent control steps. An increase in the percentage of contamination (10 to 40%) was observed during evisceration and spray washing (after evisceration), with Salmonella counts increasing from 3.9 to 5.1 log CFU per carcass. According to the prevalence of Salmonella-contaminated carcasses released to trade (20%), we estimated a risk of 272 cases of salmonellosis per year as a result of the consumption of contaminated chicken. Our study suggests that the processes of evisceration and spray washing represent a risk of Salmonella cross-contamination and/ or recontamination in broilers during slaughter line processing.